THE ROLE OF DISCIPLENE IN THE CLASSROOM - Nargiza Archabayeva Nasimovna (American Journals, 2022)
Keeping discipline is as important as teaching. Teachers who punish students to keep discipline are not often favourable. One of the main issues for every teacher, especially those just starting their careers is being able to keep discipline in class. We all have heard of well meaning new teachers who wanted to be very friendly with their students but encountered chaos when students paid no attention to them. When this problem occurs, we all know that there is no single ideal way to address the issue, so I decided to collect and summarise information for improving a bad situation in class.
Keywords: Discipline, behavior, reciprocal, misbehaving, dimension, corporal punishment